Krila "Keripik Kelapa Muda" - Kurniasari, Arismaya Wahyu; Lestari, Karina Muji; Ismuningrum, Varra Fauziah; Latif, Abdul; Utama, Rahadiyan Setya (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
Coconut is a kind of fruits which has many benefits from almost all of its parts. Unfortunately, coconut processing for consumption is somehow monotonous, especially its flesh. The white flesh of coconut is commonly used in beverages, pudding as well as cakes. The monotonous foods and beverages made of young green coconut flesh may make people get bored. This has encouraged us to make innovation in consuming coconut flesh that is by making coconut crispy chips (KRILA: Keripik Kelapa Muda). The process in making coconut crispy chips is done by using vacuum fryer, that is a kind of vacuum frying device which can keep nutrition of the coconut flesh and keep its color remain the same. The presence of KRILA is expected to give innovation in culinary related to green coconut as well as broaden job vacancy for people particularly in Malang. In order to introduce KRILA to society, several ways are done such as by distributing brochure in tourism places, campus and other public places around Veteran street; giving tester to people in those strategic places to know the societyâs favorite flavor of KRILA as well as get comment about KRILA, and doing socialization to the society. KRILA has been sold through several ways such as doing direct selling in tourism places, campus, and Veteran street; selling via BBM; and having cooperation with some stores (Toko Karina, Toko Andika, dan Toko Intan). Keywords : Sour-sop leaves, amplitude response, sensitivity, medical radiography